Analisis Pengawasan Pimpinan Pada UPTD Perlindungan Tanaman Pangan Hortikultura dan perkebunan (PTPHP) Provinsi Bengkulu - Bambang Sutikno (Jurnal STIA Bengkulu, 2022)
This study aims to identify, collect data and describe how leadership monitoring at UPTD is carried out for the protection of food crops and plantations (PTPHP) in Bengkulu province. In this study, the researchers used qualitative analysis techniques with descriptive methods, i.e. the researchers objectively described the situation related to the performance of supervisory leadership. at UPTD for Plant Protection and Cultivation Food (PTPHP) of Bengkulu Province conducted by the head of UPTD. While the data collection techniques in this study were interviews, observations and documentation. The informants for this study were 9 people, including 7 staff informants and 2 community informants. Based on the research aspects and results, one can see an overview of the performance. The first aspect is that the knowledge of UPTD PTPHP staff of Bengkulu Province about labor standards is still lacking, they do not use other means such as banners or banners and other means. The second aspect is that the working capacity of UPTD PTPHP staff in Bengkulu province to serve the community or farmers has not been maximized, due to complaints from the community or farmers that UPTD staff PTPHP of Bengkulu Province often travels on business during its work. hours and when farmers want. to provide services related to their culture. . The third aspect is that the corrective measures taken such as punishment by reprimand have not yet been able to reduce the deviations that occur.